Implementing health‐related social needs screening in western Colorado primary care practices: Qualitative research to inform improved communication with patients. (16th February 2022) - Broaddus‐Shea, Elena T.; Fife Duarte, Kelsey; Jantz, Kathryn; Reno, Jenna; Connelly, Lauri; Nederveld, Andrea
Abstract: Social determinants profoundly impact health. Many primary care practices now seek to screen their patients for health‐related social needs (HRSN) and refer them to resources in the community. However, there is little empirical evidence to guide communication with patients in order to ensure their comfort with the process and increase the likelihood that it results in positive outcomes. This paper describes the first phase of the Improving Messaging Around Gaps in Needs and rEfferals (IMAGINE) study—a multi‐phase study aiming to develop and test patient‐centred messages about screening and referral for HRSN. In this initial qualitative phase, our objective was to identify communication strategies that might make western Colorado primary care patients more comfortable with the HRSN screening and referral process. From May to July 2020 we interviewed 10 staff members responsible for HRSN screening from primary care practices participating in the western Colorado Accountable Health Communities (AHC) initiative and 20 patients from 2 of these practices. We used a rapid qualitative analysis process that involved summarising interview transcripts across key domains of interest and then identifying emergent themes within each domain using a data matrix. Through this process, we examined current communication about HRSN screening, as well as suggestions for messages and other strategies that could improve communication. In most practices, the AHC Screening Tool was handed to patients by front desk staff at check‐in with little explanation as to its purpose. Patients and staff alike recommended that patients be provided with information that: normalises the screening and referral process; assures privacy; clarifies that the purpose is to help and support rather than judge or report; emphasises community benefits; and respects patient autonomy. Interviewees also suggested broader strategies to support more effective communication, such as practice staff and clinicians building trusting relationships with patients and understanding and acknowledging the complex structural barriers that often prevent patients from accessing meaningful assistance. These findings provide actionable suggestions for improving communication about HRSN screening and referral in primary care settings. The next steps include developing specific messages based on these findings and testing their impact on screening tool completion rate, referral uptake, and patient‐reported comfort with the process.